1991
DOI: 10.1111/j.1432-1033.1991.tb16436.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies on sulfated oligosaccharides derived from the carbohydrate‐protein linkage region of chondroitin sulfate proteoglycans of whale cartilage

Abstract: From the carbohydrate-protein linkage region of whale cartilage proteoglycans, which bear predominantly chondroitin 4-sulfate, one nonsulfated, two monosulfated and one disulfated hexasaccharide alditols were isolated after exhaustive digestions with Actinase E and chondroitinase ABC, and subsequent 8-elimination. Their structures were analyzed by chondroitinase ACII digestion in conjunction with HPLC and by 500-MHz 'H-NMR spectroscopy. The nonsulfated compound (A) had the following conventional structure :

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
0
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 23 publications
4
101
0
2
Order By: Relevance
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 22 It has also been reported that xylosyltransferase, galactosyltransferases, and GlcAT-I are distributed in ER/cis-Golgi, cis-/medial-Golgi, and medial-/trans-Golgi, respectively [46]. These results suggest that nascent PGs are transported from cis-to trans-Golgi compartments during maturation, and that the sulfation of the linkage region takes place before the transfer of the first N-acetylhexosamine residue to the tetrasaccharide core and could be a signal for the differential assembly of CS and HS chains as proposed previously [7,21,26]. …”
Section: Galactosaminoglycans (Cs/ds) and Glucosaminoglycans (Hs/hep)supporting
confidence: 73%
See 3 more Smart Citations
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 22 It has also been reported that xylosyltransferase, galactosyltransferases, and GlcAT-I are distributed in ER/cis-Golgi, cis-/medial-Golgi, and medial-/trans-Golgi, respectively [46]. These results suggest that nascent PGs are transported from cis-to trans-Golgi compartments during maturation, and that the sulfation of the linkage region takes place before the transfer of the first N-acetylhexosamine residue to the tetrasaccharide core and could be a signal for the differential assembly of CS and HS chains as proposed previously [7,21,26]. …”
Section: Galactosaminoglycans (Cs/ds) and Glucosaminoglycans (Hs/hep)supporting
confidence: 73%
“…Namely, the 4-O-sulfation of a Gal-3 residue and 6-O-sulfation of both Gal-2 and Gal-3 residues have been found in CS/DS, but not HS/Hep. Interestingly, syndecan-1, a hybrid-type PG bearing both HS and CS chains, carries a 4-O-sulfate on the Gal-3 of only the CS chains [9], supporting the notion that 4-O-sulfation is a modification specific to CS chains [7]. In contrast, phosphorylation occurs on the Xyl of both CS/DS and HS/Hep [9].…”
Section: Galactosaminoglycans (Cs/ds) and Glucosaminoglycans (Hs/hep)mentioning
confidence: 91%
See 2 more Smart Citations
“…In fact, it has recently been shown that the so-called stellate cells, or lipocytes, produce 6-fold more glycosaminoglycans per cell in culture than do hepatocytes (Arenson et al, 1988 (Pertoft & Smedsr0d, 1987 Chondroitinase ABC degrades chondroitin sulphate chains to disaccharides but leaves the innermost six sugar residues (XylGal-Gal-GluA-GalNAc-GluA) intact. Of these, the GalNAc and possibly one ofthe Gal residues may be sulphated (Sugahara et al, 1988). Therefore hydrolysis of a 35SO42--labelled chondroitin sulphate chain by chondroitinase ABC will yield both radioactive disaccharides and a radioactive hexasaccharide (Hascall et al, 1972).…”
Section: Discussionmentioning
confidence: 99%